SISTEM PENGOLAHAN SAMPAH DI TEMPAT PEMBUANGAN AKHIR (TPA) MUARA FAJAR KOTA PEKANBARU - Husain, Aliamin Tabrani; Sadad, Abdul (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The amount of waste that goes into location end disposal Muara Fajar Pekanbaru City reached everyday 450,000 kg. Implementation Processing of waste in the location end disposal Muara Fajar Pekanbaru City use sanitary landfill system, sanitary landfill system is pilling up waste with systematic. implementation of the sanitary landfill system is to have positive and negative impacts for communities around location end disposal Muara Fajar Pekanbaru City. The purpose of the research for understand how to implementation waste processing system in the location end disposal Muara Fajar Pekanbaru City, and for understand influence factor waste processing system in the location end disposal Muara Fajar Pekanbaru City.This research was conducted in the location end disposal Muara Fajar District Rumbai Pekanbaru City, uses qualitative research methods to the study of descriptive data. In data collection uses observation technique and interview. The research use concept of the theory Jogiyanto author of system, system is some horde integration mutual element to achieve specific goals. The elements that represent a system in general is the input, processing, and output output. In this type system exist of one or more inputs to be processed and will produce an output.The result of this research inferential that waste system processing in the location end disposal Muara Fajar Pekanbaru City yet fully run well, because of weak supervision toward worker. Starting from input to output in the form of environmental pollution impact on soil and ground water sources in the area location end disposal Muaara Fajar Kota Pekanbaru if not properly managed in the long term. Infuence factor implementation of the waste processing system in the location end disposal Muara Fajar Pekanbaru City is lack of human resources is not adequate in terms of quantity and quality, then the infrastructure that is not supported by the activities of maintenance and repair tool, so that the waste processing system in the location end disposal Muara Fajar pekanbaru City hampered because of the condition of the damaged equipment.Kata Kunci : System, Processing